Pesquisa formativa para desenvolvimento de intervenção em comércios de alimentos no município de Santos, Brasil - Vedovato, Gabriela Milhassi [UNIFESP] (2016)
Objective. This study describes formative research used to design a food store intervention to promote healthy eating in Santos City, Brazil. Methods. We conducted a mixed-method approach in two steps: (1) Cross-sectional survey was used to evaluate associations between local food environment and household acquisition classified based on the degree of industrial food processing (n=538). Logistic regression models were adjusted to examine associations. (2) Community-based participatory study with iterative and emergent design through a community-academic partnership over a 22-month period in a low-income neighborhood in Northwest region. Data collection included participant observation, 36 community workshops, one focus group, 7 in-depth interviews, and 15 free-listings. Qualitative content data analysis was based on Social Cognitive Theory, and data triangulation was performed to evaluate social engagement, understand food-related psychosocial factors and behaviors, and inform intervention strategies. Results. Factors positively associated with minimally processed food acquisition were: frequent use of specialized markets to purchase fruits and vegetables, the habit of walking to buy food, and positive perception of food availability in participants? neighborhood. In qualitative inquiry, participants showed knowledge and intentions for healthier foods, such as rice, beans, vegetables, fruits and meats. But, there are perceived barriers to food access in local stores: high prices, low availability and variety of fresh produce, poor quality of meats, absence of a grocery delivery service and weak customer relations. Self-regulation strategies focusing on cost-effective decisions were used to overcome these obstacles and to provide enough food for the entire family. These strategies increased less healthy purchases, especially highly-processed products. In this setting, barriers were more likely to be associated with small food stores, corroborating the need for point-of-purchase interventions based on behavioral economics and social marketing to enhance healthy food choices. Conclusion. From these findings we have created a framework to comprehend how individuals in an urban low-income area make grocery-purchasing decisions. This formative assessment was useful to achieve cultural appropriateness, and to develop an effective food store trial. Community engagement showed an important role in promoting healthy eating and in sustaining local efforts to address obesity and food insecurity in this setting with limited food access.